Artificial intelligence-enabled profiling of overlapping retinal disease distribution for ocular diagnosis - Sundararajan, Sridhevi; Ramachandran, Harikrishnan; Gupta, Harshitha (IAES International Journal of Artificial Intelligence (IJ-AI), 2024)
Eyesight, an invaluable gift profoundly impacts our daily lives. In a rapidly evolving healthcare landscape, the preservation and enhancement of ocular health stand as critical objectives. This research endeavors to analyze the two retinal fundus multi-disease image datasets (RFMiD) one containing 3200 images and the other containing 860 fundus images. The primary objective of this study is to scrutinize these datasets, discern variations in the frequency of labeled diseases within and across them, and explore common combinations of labels. These findings hold important implications for the field of retinal image analysis, as they provide valuable insights into the distribution and co-occurrence of defects.